Exponential rational function method for space-time fractional differential equations - Aksoy, Esin; Kaplan, Melike; Bekir, Ahmet (TAYLOR & FRANCIS LTD, 2016)
In this paper, exponential rational function method is applied to obtain analytical solutions of the space-time fractional Fokas equation, the space-time fractional Zakharov Kuznetsov Benjamin Bona Mahony, and the space-time fractional coupled Burgers' equations. As a result, some exact solutions for them are successfully established. These solutions are constructed in fractional complex transform to convert fractional differential equations into ordinary differential equations. The fractional derivatives are described in Jumarie's modified Riemann-Liouville sense. The exact solutions obtained by the proposed method indicate that the approach is easy to implement and effective.
Keywords: 1ST INTEGRAL METHOD; COMPLEX TRANSFORM; Physics